Plant-Microbe Interactions - Insights and Views for Applications in Sustainable Agriculture - Somavarapu Thomas, Anne Sahithi; Pongprayoon, Wasinee; Cheenkachorn, Kraipat; Sriariyanun, Malinee (Applied Science and Engineering Progress, 2021)
The term “microbiome” refers to the association of plants with various microorganisms which play an important role in the niches they occupy. These microorganisms are found in the endosphere, phyllosphere, and rhizosphere, of host plants which are involved in plant ecology and physiology. The structure and dynamics of the plant microbiome have been significant seen in the last few years. In addition, the plant microbiome enhances the host plant with gene pools, which is referred to as the second plant genome or extended genome. Interestingly, the microbiome associated with plant roots has received unique attention in recent years due to its important role in host nutrition, immunity, and development. Prospective studies of the microbiome have been coupled with the need for more sustainable production for agriculture. On the other hand, various environmental factors are associated with plant-microbiome interactions that can affect composition and diversity. This review provides insights and views of plant microbiome for sustainable agriculture. Host factors that influence the microbial community, root-associated microbial consortium, commercial application, and limitation of plant microbiome were discussed. Also, this review provides current knowledge of the plant microbiome into potential biotechnology products that can be used in agricultural systems. Regardless, microbiome innovation represents the future of sustainable agriculture.